Raman spectroscopy of lymphocytes for the identification of prostate cancer patients with late radiation toxicity following radiotherapy. Issue 4 (29th June 2020) - Cullen, Daniel; Bryant, Jane; Maguire, Adrian; Medipally, Dinesh; McClean, Brendan; Shields, Laura; Noone, Emma; Bradshaw, Shirley; Finn, Marie; Dunne, Mary; Shannon, Aoife M.; Armstrong, John; et al.
Abstract: The success of radiotherapy in tumour control depends on the total dose given. However, the tolerance of the normal tissues surrounding the tumour limits this dose. It is not known why some patients develop radiation toxicity and, currently, it is not possible to predict before treatment which patients will experience adverse effects. Thus, there is an unmet clinical need for a new test to identify patients at risk of radiation toxicity. Here, we report a new approach based on Raman spectroscopy. Blood samples were collected from 42 patients who had undergone radiotherapy for prostate cancer and had shown either severe or no/minimal late radiation toxicity in follow up. Radiation response was assessed following in vitro irradiation using Raman spectroscopy in addition to the G2 chromosomal radiosensitivity assay and the γH2AX DNA damage assay. A partial least squares discriminant analysis model was developed to classify patients using known radiation toxicity scores. A sensitivity of 95%, specificity of 92% and overall accuracy of 93% was achieved. In the future, this technology may have potential to lead to individualized patient radiotherapy by identifying which patients are at risk of radiation toxicity. Abstract : There is an unmet clinical need for a new test to identify patients at risk of radiation toxicity. We report a new approach based on Raman spectroscopy of peripheral blood lymphocytes. Raman spectra were recorded from lymphocytes of prostate cancer patients who had shown severe or no/minimal late radiation toxicity in follow up. Good classification with sensitivity of 95%, specificity of 92% and overall accuracy of 93% was achieved.